Assessing the impact of the 2015 introduction of increased penalties and enhanced public awareness and enforcement activities on texting while driving among adults in Ontario, Canada. (18th May 2020) - Wickens, Christine M.; Ialomiteanu, Anca R.; Cook, Steven; Hamilton, Hayley; Haya, Maryam; Ma, Tracey; Mann, Robert E.; Manson, Heather; McDonald, André
Abstract: Objective: Texting while driving (TWD) is considered a particularly hazardous form of distracted driving. It is highly prevalent among young drivers, but fewer studies of TWD among adult drivers exist and these prevalence rates may approach those of younger drivers. The effectiveness of measures to prevent distracted driving, and TWD specifically, is unclear. On September 1, 2015, Ontario introduced increased penalties for distracted driving accompanied by public education programs to increase public awareness of the new regulations. Provincial police also introduced enhanced enforcement efforts. The current study examined self-reported TWD in a representative sample of Ontario adults before and after introduction of the new legislation and the enhanced public education and enforcement efforts. Methods: Data were based on telephone interviews with 1, 846 respondents who reported having driven in the past year. Data were derived from the 2015–2016 cycles of the Centre for Addiction and Mental Health (CAMH) Monitor, an ongoing cross-sectional telephone survey of adults aged 18+ years in Ontario, Canada. A binary logistic regression analysis of TWD in the previous 30 days was conducted, adjusting for demographic characteristics (sex, age), driving exposure, and introduction of the legislation (before versus after). Results: The proportion of the sample reporting TWD declined significantly from 37.6% before the law was introduced to 24.2% after the law was introduced. The impact appeared to be most pronounced among drivers who reported TWD more frequently. Adjusted odds of TWD declined 42% following introduction of the legislation and associated enhanced public education and enforcement. Conclusions: These results identify a decrease in TWD following the introduction of enhanced penalties with corresponding public education and enforcement efforts, adding to the existing evaluative evidence base to inform transportation safety policy. These results also support the need to examine TWD and its determinants among all age groups.